Core@shell structured flower-like Co0.6Fe2.4O4@MoS2 nanocomposites: a strong absorption and broadband electromagnetic wave absorber. Issue 29 (9th July 2019) - Long, Lin; Yang, Erqi; Qi, Xiaosi; Xie, Ren; Bai, Zhongchen; Qin, Shuijie; Zhong, Wei
Abstract : Core@shell structured flower-like Co0.6 Fe2.4 O4 @MoS2 nanocomposites and the main possible pathways of microwave absorption, strong absorption ability and broad absorption bandwidth. Abstract : In order to obtain the excellent comprehensive properties of microwave absorbers (MAs), core@shell structured Co0.6 Fe2.4 O4 @MoS2 nanocomposites were elaborately constructed and synthesized by a facile two-step hydrothermal method. Due to the independence of the two-step processes, the method could be applied to produce different categories of MoS2 based nanocomposites. The obtained results demonstrated that the as-prepared Co0.6 Fe2.4 O4 @MoS2 nanocomposites exhibited superior electromagnetic wave absorption performances with very low minimum reflection loss (RLmin ) value and broad absorption bandwidth at thin matching thicknesses. Impressively, the optimal RLmin value reached −79.9 dB at 11.2 GHz with a thickness of 2.73 mm, and an effective bandwidth of 5.96 GHz was observed with thicknesses of 2.34 and 2.98 mm. Taking into account their the low cost of production, high stability and controllability, the obtained results demonstrated that the Co0.6 Fe2.4 O4 @MoS2 nanocomposites achieved in this study are very attractive candidates for new types of high performance MAs. Moreover, we believe that constructing core@shell structured MoS2 -based nanocomposites is a reliable strategy to accelerate advancements of MAs.